An Efficient Approach for Ambulance Tracking System using GPS and GSM. Issue 1 (April 2021) - Banshwar, Anuj; Patel, Alok; Singh, Kawal Preet; Sharma, Naveen Kumar; Sharma, Bharat Bhushan; Pathak, Mohit
Abstract: An ambulance tracking system (ATS) is the need of the hour due to the recent pandemic situation going on around us. It is necessary that patients carrying vehicles such as ambulances must be equipped with the ATS technology. The ATS technology helps the hospital administration to carry out the necessary steps before the patient arrives at the hospital premises. In this technology, Global systems for Mobile communication (GSM) and Global Positioning System (GPS) are used for the efficient working of this device. In this system, a low-cost microcontroller-based electronic device Arduino is used to control the GPS and GSM modules. In this system, modem and display device such as liquid crystal display (LCD) is used at the user end which is also called as Base Station. Information regarding the location of the ambulance is provided by the GPS module. GSM module is used for communicating with the base station. The hospital administration can get the information of the arrival of the ambulance well in time and can increase the chance of survival of the patient as the time required for setting up basic components is done well in advance. This system can also be used for various other vehicles used in emergency situations.